Anomalies in the ‘dark side’ of tourism: Resistance to popular sites in Samarinda, Indonesia - Kurniawan A., Erwin; Irwansyah, Irwansyah; Hakim, Yundi Permadi; Darma, Dio Caisar (Turyzm/Tourism, 2023)
The term ‘destination security’ is found in the customs and norms applied to prevent conflicts between tourism actors, local communities and the surrounding environment. The emergence of resistance to a destination because of its ‘dark side’, both those interested or actually visiting, cannot be separated from the fact that tourists are victims of violations of the law. The purpose of this study is to explore the effect of criminal acts on the numbers of tourists in Samarinda. Operationally, the core variables are divided into material effects, non-material effects and tourist volume. The data sample focuses on local, domestic and international tourists visiting popular sites in Samarinda during 2011–2021. The results of the investigation found that both material and non-material effects contributed to reducing the volume of tourists in the short term. In the long term, the presence of extortion, theft, sexual harassment and racism seems likely to reduce the volume of tourists.